2021
DOI: 10.1021/acsaem.0c02964
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Doping and Surface Decoration of Carbon Nitride Macrostructures by Single Crystal Design

Abstract: Tailored design of hybrid carbon nitride (CN) materials is quite challenging because of the drawbacks of the solid-state reaction, and the utilization of single crystals containing C–N monomers as reactants for the high-temperature reaction has been proven to imprint a given chemical composition, morphology, or electronic structure. We report the one-pot synthesis of alkali-containing CN macrostructures with ionic crystals on its surface by utilizing a tailored melamine–hydrochloride-based molecular single cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In previous studies, it is found that the interaction of host molecules with N moieties of CN is stronger than C moieties 41 , 42 . To investigate such behaviour in the present study, the atomic RDF of N and C atoms with the adsorbed DOX molecule is calculated and given in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In previous studies, it is found that the interaction of host molecules with N moieties of CN is stronger than C moieties 41 , 42 . To investigate such behaviour in the present study, the atomic RDF of N and C atoms with the adsorbed DOX molecule is calculated and given in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…[27] Moreover, doping the material with AGA increases the surface area values up to nearly 12 m 2 g -1 (Figure S4, Supporting Infor mation) compared to 3-6 m 2 g -1 for the reference CN derived www.advopticalmat.de from melamine hydrochloride. [18,20] Transparent colloidal solu tions were achieved by exposing a suspension of the prepared CN materials in ethanol (0.1 mg mL -1 ) to strong sonication for 1 h, followed by centrifugation to remove residual aggregates. The resulting CN materials display a thin nanosheet mor phology, with lateral sizes up to several micrometers, as shown by transmission electron microscopy (TEM), which revealed that the materials also contain smaller aggregates of up to 200 nm in lateral dimensions (Figure S5, Supporting Infor mation).…”
Section: Resultsmentioning
confidence: 99%
“…[17] Notably, highly ordered supramolecular single crystals have been shown to be particularly useful in this regard. [18][19][20] In this work, we exploited these findings to synthesize new triazine based cocrystals composed of melamine and acetoguanamine (AGA), which were subsequently used as precursors for CN via hightemperature reaction. We tuned the precursor crystalline structures to endow the final CNs with a good photolumines cent behavior in both liquid and solid states, as demonstrated by their performance in detecting metal ions (in an aqueous environment) and labeling latent fingerprints (as a solidstate sensing platform).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the utilization of highly ordered supramolecular single crystals based on CN monomers has been exploited as an effective approach to control the properties of CN materials [ 155 , 156 ]. Barrio et al, synthesized melaminium chloride hemihydrate single crystals, where protonated melaminium were connected by Cl − and H 2 O [ 157 ].…”
Section: Pore Modifications Over G -C 3 Nmentioning
confidence: 99%